High-Speed Running and Sprinting Thresholds in Elite Female Team Sports: A Systematic Review - Raúl Nieto-Acevedo; Alfonso de la Rubia; Enrique Alonso-Pérez-Chao; Moisés Marquina Nieto; Carlos García-Sánchez (Applied Sciences)
Over the past decade, participation in female team sports has increased significantly, leading to greater interest in monitoring their training and competition load using wearable technology. Despite this, there is currently no systematic review or meta-analysis that has specifically focused on quantifying and comparing high-speed running (HSR) and sprinting thresholds in female team sports. This systematic review aimed (1) to summarize and describe the evidence on absolute speed thresholds used to classify HSR and sprinting in female team sports and (2) to compare HSR and sprinting thresholds between female team sports. A total of 82 studies were included, encompassing a range of female team sports such as Australian football, basketball, field hockey, soccer, Gaelic football, handball, lacrosse, and different codes of rugby (league, sevens, and union). This systematic review was conducted following the PRISMA 2020 guidelines. This review found that to date, there is no consensus on defining high-speed and sprint running thresholds in female team sports, showing considerable variability in the thresholds used to define HSR (ranging from 11.1 to 21.6 km·h⁻1) and sprinting (from 15.0 to 30.0 km·h⁻1). Our results showed that the mean velocity for the HSR threshold was 16 km·h⁻1, although the most frequently used velocity was 18.0 km·h⁻1. In relation to the sprint threshold, the mean and the mode were similar: 21 km·h⁻1 and 20.0 km·h⁻1, respectively. The lack of standardized thresholds highlights the need for personalized approaches when monitoring training loads in female athletes. Despite apparent variability, these findings provide valuable insights for practitioners in designing evidence-based training programs aimed at optimizing high-speed exposure in female team sports. Further research is needed to establish sport-specific and standardized velocity thresholds for women’s team sports.